Time and temperature dependent multiple hierarchical NiCo2O4 for high-performance supercapacitors. Issue 17 (5th April 2016) - Wang, Shen; Sun, Shumin; Li, Shaodan; Gong, Feilong; Li, Yannan; Wu, Qiong; Song, Pei; Fang, Shaoming; Wang, Peiyuan
Abstract : The time and temperature dependent multiple hierarchical NiCo2 O4 constructed of nanosheets covered with nanowires shows excellent electrochemical performance. Abstract : A multiple hierarchical NiCo2 O4 (denoted as P-100), which was constructed of nanosheets covered with nanowires, was obtained by a facial hydrothermal method in combination with annealing treatment at 300 °C. The hydrothermal temperature and reaction time play key roles in the formation of the unique hierarchical NiCo2 O4 based on the morphology evolution. As a supercapacitor electrode material, the obtained P-100 displays a high specific capacitance of 1393 F g −1 at 0.5 A g −1 . Furthermore, the assembled P-100//AC asymmetric supercapacitor demonstrates a high energy density (21.4 Wh kg −1 ) at a power density of 350 W kg −1 and remarkable cycling stability. The good electrochemical performances of the P-100 are mainly due to its three dimensional hierarchical porous nanostructure and high specific surface area as well as the synergetic effect of the nanosheets and nanowires in NiCo2 O4 . The experimental results demonstrated that the multiple hierarchical NiCo2 O4 is a promising electrode material for high-performance supercapacitors.